Characterization of application scenario-dependent pharmacokinetics and pharmacodynamic properties of permethrin and hyperforin in a dynamic skin and liver multi-organ-chip model. (30th January 2021) - Kühnl, Jochen; Tao, Thi Phuong; Brandmair, Katrin; Gerlach, Silke; Rings, Thamée; Müller-Vieira, Ursula; Przibilla, Julia; Genies, Camille; Jaques-Jamin, Carine; Schepky, Andreas; Marx, Uwe; Hewitt, Nicola J.; et al.
Highlights: Application of skin-liver HUMIMIC Chip2, a multi-organ chip technology. Hyperforin and permethrin pharmacokinetics and dynamics measured. Fate of chemicals impacted by dose route and frequency. Liver spheroid gene expression dependent on dosing scenario. Chip2 model relevant to risk assessment of topically applied cosmetics ingredients. Abstract: Microphysiological systems (MPS) aim to mimic the dynamic microenvironment and the interaction between tissues. While MPS exist for investigating pharmaceuticals, the applicability of MPS for cosmetics ingredients is yet to be evaluated. The HUMIMIC Chip2 ("Chip2″), is the first multi-organ chip technology to incorporate skin models, allowing for the topical route to be tested. Therefore, we have used this model to analyze the impact of different exposure scenarios on the pharmacokinetics and pharmacodynamics of two topically exposed chemicals, hyperforin and permethrin. The Chip2 incorporated reconstructed human epidermis models (EpiDerm™) and HepaRG-stellate spheroids. Initial experiments using static incubations of single organoids helped determine the optimal dose. In the Chip2 studies, parent and metabolites were analyzed in the circuit over 5 days after application of single and repeated topical or systemic doses. The gene expression of relevant xenobiotic metabolizing enzymes in liver spheroids was measured to reflect toxicodynamics effects of the compounds in liver. The results show that 1) metabolic capacities of EpiDerm™ and liver spheroids were maintained over five days; 2) EpiDerm™ model barrier function remained intact; 3) repeated application of compounds resulted in higher concentrations of parent chemicals and most metabolites compared to single application; 4) compound-specific gene induction e.g. induction of CYP3A4 by hyperforin depended on the application route and frequency; 5) different routes of application influenced the systemic concentrations of both parents and metabolites in the chip over the course of the experiment; 6) there was excellent intra- and inter-lab reproducibility. For permethrin, a process similar to the excretion in a human in vivo study could be simulated which was remarkably comparable to the in vivo situation. These results support the use of the Chip2 model to provide information on parent and metabolite disposition that may be relevant to risk assessment of topically applied cosmetics ingredients.